The Emergence of Sociopreneurship among Youth: A Phenomenological Study - Aryan Agus Pratama; Aris Baharuddin; Fatimah Akbal; Leonardo Davidsi Sipayung; Zohaib Hassan Sain (Universitas Bumigora, 2026)
The development of social entrepreneurship among the younger generation reveals new dynamics in integrating social and economic activities to ensure the sustainability of social impact. However, most studies still focus on structural aspects and outcomes, and thus have not yet adequately explained how social entrepreneurship emerges from individual social experiences. This study aims to investigate how social entrepreneurship emerges among the younger generation as a transformation from social prac- tices toward economic integration. The method used is a phenomenological qualitative approach. Data were collected through participant observation, in-depth interviews with three key informants, and doc- umentation. Data analysis was conducted inductively through data condensation, data presentation, and conclusion drawing, aided by coding techniques. The research findings indicate that the formation of sociopreneurship is influenced by three main dynamics: social initiation, resource mobilization, and the formalization of practices. This process emphasizes that engagement in social activities serves as the foundation for developing an action orientation, which subsequently evolves into more structured practices. The integration of economic dimensions emerges as a response to the need to sustain these activities, rather than as an initial goal. This study contributes by affirming that sociopreneurship is an emergent process rooted in social experience, broadening the perspective from a structural approach toward a process-oriented one. The implications of this study encourage strengthening social practice- based approaches to develop more contextual and sustainable sociopreneurship.